Environmental implications of higher ethanol production and use in the U.S.: A literature review. Part II – Biodiversity, land use change, GHG emissions, and sustainability - Hoekman, S. Kent; Broch, Amber (Renewable & sustainable energy reviews, 2018)
To address issues of energy security and greenhouse gas (GHG) mitigation, substantial amounts of corn-derived ethanol are being used in U.S. gasoline. Currently, ethanol comprises 10% of the U.S. gasoline pool (E10), but there is interest in increasing this – possibly doubling the amount currently used. Production of corn ethanol raises several concerns with respect to environmental and ecological impacts. This paper reviews the available literature regarding impacts on biodiversity, land use change (LUC), greenhouse gas (GHG) emissions, and overall sustainability. A companion paper addresses impacts on water, soil, and air quality. We emphasize recent information appearing since comprehensive reports on these topics were issued by the U.S. EPA and NRC/NAS in 2011. The principal environmental and ecological concerns arise from the intensive agricultural activities associated with corn cropping. Expansion of these activities promotes regional mono-culture, which is accompanied by reduced plant and animal biodiversity, and diminished ecosystem functions and services. Extensification of corn cropping into Conservation Reserve Program (CRP) lands is occurring, which raises concerns about erosion, nutrient runoff, and other adverse environmental impacts. Estimating the impacts of increased ethanol on GHG emissions requires sophisticated life cycle assessment (LCA) modeling approaches to account for emissions resulting from land use change (LUC). Although considerable uncertainty remains, recent regulatory modeling by EPA and CARB estimate modest GHG reductions of about 20% from corn ethanol as compared to gasoline. Being a major commodity in global food/feed markets, displacing large amounts of corn to produce ethanol strengthens demand and increases prices. To date, these effects have been small, but there are growing concerns about increased use of staple food products to produce fuels within the context of an expanding global population that faces severe calorie shortages. Tradeoffs regarding environmental, ecological, and social impacts raise questions about the overall sustainability of such an approach.